Meningkatkan Kesiapan Siswa TK Yaa Bunayya Lodoyo Untuk Menerapkan “New Normal Life” Pada Pandemi Covid 19 - Anita Rahmawati; Yeni Kartika Sari; Ning Arti Wulandari (Community Development Journal, 2020)
The covid-19 pandemic that occurred in the world, including Indonesia, encouraged the government to urge people to adopt new normal habits as a measure to prevent the transmission of covid 19. The community, especially parents and students of Yaa Bunayya Lodoyo Kindergarten, still do not have optimal knowledge and behavior to prevent Covid-19 transmission. This community service aims to improve the readiness of TK Yaa Bunayya Lodoyo students to implement "new normal life" by increasing the knowledge of parents and students in preventing Covid 19 transmission. the second stage of education with video media provided to students. This activity was attended by 27 parents / guardians and 51 TK Yaa Bunayya Lodoyo students. The data were collected using a questionnaire and the data were analyzed using the paired t-test statistical test. Service results show that parents' knowledge and student behavior have increased significantly.